A three-dimensional dental model restoration method based on tooth feature contours. Issue 9 (15th July 2021) - Yang, Shuai; Zhao, Wenjie; Ke, Yongzhen; Liu, Jiaying; Xue, Yongjiang
Abstract : Purpose: Due to the inability to directly apply an intra-oral image with esthetic restoration to restore tooth shape in the computer-aided design system, this paper aims to propose a method that can use two-dimensional contours obtained from the image for the three-dimensional dental mesh model restoration. Design/methodology/approach: First, intra-oral image and smiling image are taken from the patient, then teeth shapes of the images are designed based on esthetic restoration concepts and the pixel coordinates of the teeth's contours are converted into the vertex coordinates in the three-dimensional space. Second, the dental mesh model is divided into three parts – active part, passive part and fixed part – based on the teeth's contours of the mesh model. Third, the vertices from the teeth's contours of the dental model are matched with ones from the intra-oral image and with the help of matching operation, the target coordinates of each vertex in the active part can be calculated. Finally, the Laplacian-based deformation algorithm and mesh smoothing algorithm are performed. Findings: Benefitting from the proposed method, the dental mesh model with esthetic restoration can be quickly obtained based on the intra-oral image that is the result of doctor-patient communication. Experimental results show that the quality of restoration meets clinical needs, and the typical time cost of the method is approximately one second. So the method is both time-saving and user-friendly. Originality/value: The method provides the possibility to design personalized dental esthetic restoration solutions rapidly.